1995
DOI: 10.1042/bj3090959
|View full text |Cite
|
Sign up to set email alerts
|

The chloride effect in the human embryonic haemoglobins

Abstract: The interactions of the three human embryonic haemoglobins with chloride ions have been investigated. Each of the three embryonic haemoglobins exhibits a unique pattern of oxygen-affinity-dependence on chloride ion concentration. Human embryonic haemoglobin Portland (zeta 2 gamma 2) is found to be completely insensitive to chloride ion concentration. Haemoglobin Gower I (zeta 2 gamma 2) shows a small concentration dependence, whilst haemoglobin Gower II (alpha 2 epsilon 2) exhibits a dependence approaching tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 16 publications
2
14
0
Order By: Relevance
“…Differences in Cl -sensitivity are associated with differences in Cl -binding constants: 0.127±0.027moll -1 and 0.104±0.025moll -1 for highland and lowland mice, respectively. These values are similar to those for other vertebrate Hbs (Antonini and Brunori, 1971;Weber, 1992;Hofmann et al, 1995) and are close to the Cl -concentration normally present in the vertebrate red blood cell (0.1moll -1 ). A relatively greater allosteric effect of Cl -ions than of DPG on Hb-O 2 affinity has also been reported for house mice Mus musculus (Runck et al, 2010), and may be a feature shared by other rodents.…”
Section: -Bindingsupporting
confidence: 87%
“…Differences in Cl -sensitivity are associated with differences in Cl -binding constants: 0.127±0.027moll -1 and 0.104±0.025moll -1 for highland and lowland mice, respectively. These values are similar to those for other vertebrate Hbs (Antonini and Brunori, 1971;Weber, 1992;Hofmann et al, 1995) and are close to the Cl -concentration normally present in the vertebrate red blood cell (0.1moll -1 ). A relatively greater allosteric effect of Cl -ions than of DPG on Hb-O 2 affinity has also been reported for house mice Mus musculus (Runck et al, 2010), and may be a feature shared by other rodents.…”
Section: -Bindingsupporting
confidence: 87%
“…As with DPG, we found the chloride sensitivity (Log P 50 Hofmann et al 1995). It has been shown that the difference between the two human Hbs (i.e.…”
Section: Oxygen Affinitymentioning
confidence: 59%
“…For the family of three human embryonic hemoglobins produced during the embryonic stage of human development, the situation is somewhat more complex. The two f chain-containing proteins are almost devoid of a response to chloride ions, whereas the a 2 e 2 protein (hemoglobin Gower II) shows a substantial chloride ion response, which is 40% less than that seen in the case of the adult protein (6). These differences in response observed for the f chain-containing proteins can, in the main, be explained in terms of amino acid differences at the sites identi ed as controlling the chloride effect in the adult protein (3).…”
Section: Introductionmentioning
confidence: 88%
“…In the case of the a 2 e 2 protein, however, the diminished chloride ion effect does not correspond to any simple replacement of these key amino acids. Close comparison of the amino acid sequences of the embryonic e and adult b chains has lead to the suggestion that any of three possible amino acid changes between the chains might be responsible for the lowering of the sensitivity towards chloride ions observed in the e chain-containing protein (6). The three residues proposed as possible candidates are His b 116!…”
Section: Introductionmentioning
confidence: 99%